ANALYSIS OF DETERMINING STRATEGIC POSITION USING A SWOT APPROACH AT EARTH ISLAMIC RELIGIOUS SCHOOL OF SILAMPARI LUBUKLINGGAU - Yohanes Susanto; Indan Winarni; Effendi (Manajemen Bisnis, 2021)
The purpose of this study is to analyze the strategic position of the Bumi Silampari Islamic High School (STAI) in Lubuklinggau City, South Sumatra, at this time and its development in the future. This research method uses a SWOT approach with a total of 13 respondents who are elements of the leadership of STAI Bumi Silampari, based on data described from the external environment and internal environment, the results show that the position of Islamic religious high schools is currently in the quadrant (IA) graph. Cartesius is a stable growth strategy, meaning that STAI Bumi Silampari can grow according to its capabilities, even though business opportunities are still available, however, the growth of STAI Bumi Silampari cannot be fast, but gradually, because the relatively large opportunities are exploited by competitors. , STAI Bumi Silampari must maximize the strengths it currently has, by identifying business opportunities and exploiting them by improving infrastructure and physical facilities of buildings and public facilities, as well as improving the quality of lecturers and appropriate compensation, as a strategy to maintain reliable human resources